Respuesta :
Answer: Your complete answer would be -2x^9, if I'm not mistaken.
For this case we must find the quotient resulting from dividing the following expressions:
[tex]\frac {-8x ^ 6} {4x ^ {- 3}} =[/tex]
By definition of power properties, we have to:
[tex]a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}[/tex]
Then, we can rewrite:
[tex]4x ^ {- 3} = \frac {4} {x ^ 3}[/tex]
So:
[tex]\frac {-8x ^ 6} {\frac {4} {x ^ 3}} =\\\frac {-8x ^ 6 * x ^ 3} {4} =[/tex]
By properties of multiplication of powers we have:
[tex]a ^ n * a ^ m = a ^ {n + m}[/tex]
So:
[tex]\frac {-8x ^ 9} {4} =\\-2x ^ 9[/tex]
Answer:
[tex]-2x ^ 9[/tex]